Direct seed farming of cabbage in Derbent district of Republic of Dagestan - Sergey M. Sirota; Lyudmila L. Bondareva; Kurbangadzhi N. Veliev (Овощи России, 2019)
Relevance The Republic of Dagestan is the southernmost region in the Russian Federation. The climatic conditions of the Derbent district of the Republic of Dagestan are favorable for seed production without direct cabbage. Material and method In cabbage seed production in direct culture it is necessary to take into account the peculiarities of cabbage biology. In the Republic of Dagestan near the city of Derbent, all the phasic processes near cabbage take place in a short autumn period and in early spring. Results Years of experience in the conduct of cabbage seed production made it possible to determine the optimal timing for planting varieties (parental hybrids) of white cabbage of different groups of ripeness and different varieties. The technology of direct seed farming of cabbage is presented.